An electrically driven structural phase transition in single Ag2Te nanowire devices. Issue 14 (21st March 2019) - Premasiri, Kasun; Zheng, Wei; Xu, Biao; Ma, Tao; Zhou, Lin; Wu, Yue; Gao, Xuan P. A.
Abstract : Exploring new phase-change materials is instrumental in the progression of electronic memory devices. Abstract : Exploring new phase-change materials is instrumental in the progression of electronic memory devices. Ag2 Te with its reversible structural phase transition, and in the form of nanowires, has become an apt candidate for potential use in nanoscale memory devices. Here, we report a study on the temperature- or electrically-driven phase change properties of crystalline Ag2 Te nanowires. We first demonstrate that this structural phase change can be achieved via heating up the nanowires, which results in a sharp drop in conductance. Then we show that a DC voltage (<1 V) induced Joule heating can be used to reach the phase transition, even without any external heating. This work shows the potential of using Ag2 Te nanowires as a phase-change material in low voltage and low power nanoscale devices.